REFLECTIVE SOCIAL WORK EDUCATION IN SUPPORT OF SOCIALLY JUST SOCIAL WORK PRACTICE: THE EXPERIENCE OF SOCIAL WORK STUDENTS AT A UNIVERSITY IN SOUTH AFRICA - Merlene Esau; Anneline Keet (Social Work/Maatskaplike Werk, 2014)
Social justice and human dignity are core components of social work principles and ethics; therefore social work education should lead to socially just practice. Social workers’ ability to practise in a socially just manner relies significantly on their ability to reflect on the influence of their personal and professional socialisation and the structural inequalities that influence the lives of service users. In order to achieve a deep sense of social justice, social workers should be educated to be critical, responsive practitioners who can observe, ask questions and fight against inequalities.